Croatia’s Science and Technology Project Unleashes Innovation - Correa, Paulo; Tarade, Ljiljana; Borowik, Iwona M. (World Bank, Washington, DC, 2012)
Croatia's economic and social development achievements in the last decade have been impressive; the country closed its income gap with the European Union and now has some of the best social development indicators in the region. However, growing current account deficits, in the context of increasing domestic wages, small productivity gains and scarce innovation, suggest that this pattern may not be sustainable. With the economic crisis hitting the region hard, accelerating productivity and reaping the benefits of innovation for the country's development have become even more urgent.